Effect of Resin-modified Glass Ionomer Cement Dispensing/Mixing Methods on Mechanical Properties - Sulaiman, T A; Abdulmajeed, A A; Altitinchi, A; Ahmed, S N; Donovan, T E (Operative dentistry, 2018)
Resin-modified glass ionomer cements (RMGIs) are often used for luting indirect restorations. Hand-mixing traditional cements demands significant time and may be technique sensitive. Efforts have been made by manufacturers to introduce the same cement using different dispensing/mixing methods. It is not known what effects these changes may have on the mechanical properties of the dental cement. The purpose of this study was to evaluate the mechanical properties (diametral tensile strength [DTS], compressive strength [CS], and fracture toughness [FT]) of RMGIs with different dispensing/mixing systems. The RMGI specimens (n=14)-RelyX Luting (hand mix), RelyX Luting Plus (clicker-hand mix), RelyX Luting Plus (automix) (3M ESPE), GC Fuji PLUS (capsule-automix), and GC FujiCEM 2 (automix) (GC)-were prepared for each mechanical test and examined after thermocycling (n=7/subgroup) for 20,000 cycles to the following: DTS, CS (ISO 9917-1) and FT (ISO standard 6872; Single-edge V-notched beam method). Specimens were mounted and loaded with a universal testing machine until failure occurred. Two-/one-way analysis of variance followed by Tukey honestly significantly different post hoc test was used to analyze data for statistical significance ( p<0.05). The interaction effect of both dispensing/mixing method and thermocycling was significant only for the CS test of the GC group ( p<0.05). The different dispensing/mixing methods had no effect on the DTS of the tested cements. The CS of GC Fuji PLUS was significantly higher than that of the automix version ( p<0.05). The FT decreased significantly when switching from RelyX (hand mix) to RelyX Luting Plus (clicker-hand mix) and to RelyX Luting Plus (automix) ( p<0.05). Except in the case of the DTS of the GC group and the CS of GC Fuji PLUS, thermocycling had a significant effect reducing the mechanical properties of the RMGI cements ( p<0.05). Introducing alternative dispensing/mixing methods for mixing RMGIs to reduce time and technique sensitivity may affect mechanical properties and is brand dependent.